The eye of the storm: a feasibility study of an adapted Mindfulness-based Cognitive Therapy (MBCT) group intervention to manage NHS staff stress. (December 2014) - Marx, Robert; Strauss, Clara; Williamson, Cleo; Karunavira,; Taravajra,
Abstract: A feasibility study evaluated five adapted Mindfulness-based Cognitive Therapy (MBCT) groups that were delivered to staff in a National Health Service (NHS) mental health Trust as part of a staff health and wellbeing initiative. Using an uncontrolled design typical of a feasibility study, recruitment, retention and acceptability of the groups were assessed. Effectiveness was also measured at pre- and post-therapy, and at 3-month follow-up, using quantitative methods. In addition, qualitative methods were used to explore staff experiences of the groups. Results demonstrated high levels of feasibility, and significant improvements in staff perceived stress and self-compassion at both post-therapy and follow-up. Qualitative data suggested many staff felt the groups had improved their physical and emotional health, their ability to manage stress at work and the quality of their work with patients and of their relationships with colleagues. Although Mindfulness-based Stress Reduction (MBSR) has typically been used to help manage staff stress, these results are promising for the use of an adapted MBCT with this population. Challenges and factors contributing to these outcomes are discussed.